MEMBIMBING GENERASI Z DAN ALPHA: STRATEGI KEPEMIMPINAN KRISTEN DALAM ERA DIGITAL - Yurisman Lafau; Anwar Three Millenium Waruwu; Ruth Judica Siahaan (TEOLOGIS, RELEVAN, APLIKATIF, CENDIKIA, KONTEKSTUAL, 2024)
Abstract Generation Z and Alpha, born in the digital era, face unique challenges in an ever-evolving technological environment. This article aims to provide a comprehensive understanding of the relevant concepts, models, and strategies of Christian leadership within this digital generation's context. With a focus on Generation Z and Alpha, this research explores the impact of implementing Christian leadership in addressing the dynamics of the digital era. Through a literature review approach, this article identifies crucial stages in qualitative research, including topic identification, literature search and selection, analysis, synthesis, and interpretation of findings. The results show that the concept of Christian leadership, emphasizing spiritual service and Gospel testimony, is highly relevant in facing the challenges of this digital generation. Innovative and adaptive leadership strategies, such as utilizing digital platforms to build online communities and strengthen authentic relationships, are found effective in reaching Generation Z and Alpha. The application of Christian leadership models also provides both short-term and long-term positive impacts, including spiritual guidance, church community strengthening, and empowering young leaders. Overall, this research makes a significant theoretical and practical contribution to the development of effective and relevant Christian leadership strategies in the digital era while upholding the values and teachings of Christ. Keywords: Generation Z, Generation Alpha, Christian leadership, digital era, innovative and adaptive.